Letter to the Editor. Issue 5 (3rd September 2019) - Inbar, Efraim; Shaver, Benjamin L.; Ziv, Guy
Abstract : The key issue is whether the minimum Israeli security conditions for the establishment of a Palestinian state can be fulfilled.